Redesigning the Games? The 2020 Olympic Games, Playbooks and new sports event risk management tools - Ludvigsen, J. A. L.; Parnell, D. (Managing Sport and Leisure, 2023)
Rationale/Purpose: More than a year into the pandemic, scholars and practitioners have highlighted several of the organizational implications of coronavirus-disease 2019 (COVID-19) on worldwide cultural festivals and sporting events. Following COVID-19, numerous major sporting events, including the 2020 Tokyo Summer Olympics, were postponed in February and March 2020. As the new dates of many rescheduled sporting events approach in time, the article discusses pressing questions related to sporting event risk, safety and security. Design/Methodology/Approach: The paper is conceptual and employs insights and frames from the risk management literature for its examination of sporting events staged in the mid- and late 2020 and early 2021. Findings: We analyse risk management strategies and safety practices at recent sporting events that have been staged throughout the pandemic. Our argument is that the rescheduled sporting events - exemplified by the 2020 Olympics - have been subject to organizational, social and spatial redesign processes. Practical Implications: The paper can provide emerging lessons and considerations for sporting event stakeholders in the face of the COVID-19 pandemic. Research Contributions: The paper adds to our understanding of emerging risk management strategies and safety practices that event stakeholders have adopted in the context of COVID-19. This is supplemented by an emerging and multidisciplinary research agenda.